(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Alyousif NA. 2021. Distribution, occurrence and molecular characterization of Bacillus related species isolated from different soil in Basrah Province, Iraq. Biodiversitas 23: 679-686. Bacillus related species are widely predominant in various environments such as soil with diverse environmental conditions. These bacteria are one of the most explored groups of bacteria in industrial biotechnology due to their enzymes. The present study was aimed to isolate, screen and determine the distribution of Bacillus related species from soil samples. The total Bacillus related species counts in one gram of each soil sample ranged between 3.2 X 103 cfu/g and 4 X 103 cfu/g. A total of 43 isolates with different morphologies were isolated from the soil samples out of ten different habitats and the number of morphotypes recovered from each habitat varied from 2 to 7. The molecular identification of isolates by PCR technique and sequencing of 16S rDNA gene indicated that 43 isolates belonged to the genera Bacillus, Cytobacillus, Priestia and Peribacillus. The species Bacillus licheniformis and Bacillus subtilis were the most distributed species in the habitats. The bacterial isolates were showed 100% similarity, except 8 isolates were showed 99% similarity were identified as new strains and their sequences were deposited at the National Center for Biotechnical Information (NCBI). The phylogenetic tree was constructed by MEGA X software based on 16S rDNA gene sequences of Bacillus related species to evaluate their close relationship and evolution. The study revealed the higher diversity and distribution of Bacillus related species in the soil samples and the molecular technique was the best method for identifying Bacillus related species.